Indigenous potters in Hispania Citerior. A Catalogue of vernacular names in potter stamps - Simón Cornago, Ignacio (Gerión. Revista de Historia Antigua, 2018)
The aim of this paper is to make a catalogue of the indigenous personal names attested in the potter stamps of the Roman province of Hispania Citerior. The stamps are on dolia, ware ceramics, tegulae, lateres and terra sigillata.
Keywords: Celtiberian onomastic; Potter stamps; Pottery; Potter’s workshop; Tritium Magallum; Segobriga.